Irrigation, health and environment: a review of literature from Turkey - Harmancioglu, N.; Alpaslan, N.; Boelee, Eline (International Water Management Institute, 2001)
This report is intended to serve as reference and guide for researchers and policy makers linked to water resources development in Turkey and elsewhere. The topics covered include: recent developments in the water sector, the epidemiology and control of malaria and schistosomiasis, the use and effects of pesticides in irrigated agriculture, water quality issues and standards and the relationship between irrigation and wetlands.